Bursting with anxiety: Adult social referencing in an interpersonal Balloon Analogue Risk Task (BART) - Parkinson, B; Phiri, N; Simons, G (American Psychological Association, 2012)
This study developed an interpersonal modification of the Balloon Analogue Risk Task (BART) to assess effects of a friend’s real-time facial expressions on co-participants’ risk-taking. Twenty pairs of male friends and 20 pairs of female friends completed two counterbalanced versions of BART, one framed in terms of monetary gain, and the other framed in terms of avoiding loss. Each pair included a player who performed the task across both trials and a reference person in a separate cubicle connected via a soundless video link. In the suppression condition, reference persons were told to minimise facial expressions of anxiety as balloons inflated. In the expression condition, they were told to freely express anxiety. As predicted, players took greater risks and burst more balloons in the suppression condition, but only under the gain frame. Players’ BART scores across both frames were also significantly negatively correlated with reference persons’ scores on a questionnaire measure of dispositional expressivity (BEQ), confirming that other people’s expressions can moderate own risk-taking.